Leveraging CSR to achieve MDGs: a case study of Ghana - Bussa, Carla (2012)
The Millennium Development Goals possibly embody the most powerful challenge the world was ever confronted with in order to achieve sustainable global development. The potential role that the private sector can play in it is growingly been emphasised and the CSR/Development debate in relation to developing countries is rising to prominence.